ANALYSIS OF THE PARTNERSHIP PROGRAM'S EFFECTIVENESS IN DISTRIBUTING LOANS AND COLLECTING LOANS AS BUMN PKBL RESPONSIBILITIES FROM 2017 TO 2019 - Rahmat Yuliansyah; Desy Amaliati Setiawan; Bayu Pratama (LPSDI Bina Patria, 2023)
The purpose of this study is to evaluate the efficacy of partnership program credit distribution and credit collecting as a means of BUMN PKBL accountability in 2017–2019. This study combines descriptive analysis with quantitative research. All State-Owned Enterprises (BUMN) that engage in PKBL operations from 2017 to 2019 comprise the study's population. With the criteria that the company has published complete data in the Partnership and Community Development Program sector and has the necessary financial data in measuring all variables in this study, the sample is determined using the slovin formula, resulting in a total of 7 companies being sampled in this study. The information used in this study is secondary information. Methods for gathering data from each company's official website. Using Microsoft Excel and the calculation formula from the Decree of the Minister of BUMN Number KEP-100/MBU/2002, this research was processed. The effectiveness of credit distribution (PK) and the degree of credit collecting of each BUMN utilized as a sample are both examined in this study. The findings demonstrated that all businesses were quite adept at meeting their obligations in the area of partnership initiatives (PK). BUMN generally disburses loans quite successfully, but there are still some businesses who distribute their partnership program loans ineffectively. Similar circumstances apply to the collecting rate for loan repayments, where certain BUMN have low collecting rates and others have rather high rates.